Insecure Attachment, Emotion Dysregulation, and Psychological Aggression in Couples - Cheche Hoover, Rachel (Journal of interpersonal violence, 2021)
According to adult attachment theory, levels of insecure attachment—both anxious and avoidant—are associated with abilities to regulate emotions in a relational context. This study is the first to test emotion dysregulation as a mediator of the association between levels of insecure attachment and psychological aggression using dyadic data. Cross-sectional self-report data were collected from 124 couples presenting for couple or family therapy at an outpatient clinic. Path analysis was used to analyze an actor–partner interdependence mediational model. Results did not support emotion dysregulation mediating the association between level of anxious attachment and psychological aggression, or the association between level of avoidant attachment and psychological aggression. Results indicated a direct actor effect between level of anxious attachment and psychological aggression for women (β = .19, p = .045) and men (β = .19, p = .027). Direct partner effects between people’s own levels of anxious attachment and their partners’ psychological aggression for women (β = .28, p = .001) and men (β = .33, p = .001) were also identified. Results also indicated direct actor effects between anxious attachment and emotion dysregulation in both women (β = .51, p < .001) and men (β = .58, p < .001), whereas direct actor effects between avoidant attachment and emotion dysregulation were only identified among women (β = .32, p < .001). Results suggest that increasing partners’ abilities to effectively manage their own maladaptive attachment-related behaviors may decrease levels of psychological aggression between partners. Limitations and clinical implications for couple therapists are discussed.